Pengaruh Risiko Bisnis, Ukuran Perusahaan dan Pertumbuhan Penjualan Terhadap Struktur Modal pada Sektor Food and Beverage - Marinus Ronal; Chrismesi Pagiu (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to test and analyze the effect of risk, company size and sales growth on capital structure in the food and beverage sector on the Indonesia Stock Exchange. The sample in this study was 5 companies that were selected using sample determination criteria. The analysis techniques used were classical assumption tests, hypothesis tests and coefficient of determination. The results showed business risk with a coefficient value of 0.136, company size 0.003, sales growth 0.704 and simultaneously had an effect with a coefficient value of 0.019.